Pengaruh Waktu Dan Suhu Pretreatment Ampas Tebu Menggunakan Asam Sulfat Encer - Astri Gusrita; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Currently, Indonesian is still relies on non-renewable energy sources (fossil). One of alternative to replace fossil fuel is with bioenergy such as bioethanol. Bioethanol can be produced from lignocellulose biomass such as sugarcane bagasse. Sugarcane bagasse is lignocellulose biomass with 39,26% cellulose, 7,49% hemicellulose, and 23,48% lignin. To take cellulose contained in sugarcane bagasse, a pretreatment process is needed. Pretreatment process is the process of removing lignin from cellulose. The purpose of this study is to determine the optimum conditions of the pretreatment process with time and temperature variation. The stages that carried out in this study are raw material preparation, pretreatment, and analysis. Preparation of raw materials is cutting bagasse up to 0,5 cm and dry it at room temperature. The pretreatment process used acid solvent with low concentrations of H2SO4 0,5 M with time variations of 30 minutes, 60 minutes, 90 minutes, and temperature variations of 60oC, 80oC, 100oC. Pretreatment analysis was performed using the Chesson-Datta method. The optimum pretreatment conditions in this study were at time variation of 60 minutes and temperature of 80oC, with 62,84% cellulose and 19,88% residual lignin. The temperature used in the pretreatment affects the length of time needed for the process to get optimum results. Keywords: cellulose, lignin, pretreatment, sugarcane bagasse